PEMODELAN COPULA CLAYTON UNTUK PREDIKSI KLAIM PADA DATA LONGITUDINAL DENGAN EXCESS ZEROS - Anaviroh, Anaviroh; Effendie, Adhitya Ronnie (UJMC (Unisda Journal of Mathematics and Computer Science), 2018)
This papper discuss about longitudinal data models of claim counts with excess-zeros, in which time-dependence of the claim counts is modeled by using a copula function. The copula approach extensively to model the serial dependence of the claim counts in car insurance, to model this serial dependence of the claim counts (between the history and future claims). The maximum likelihood is applied to estimate the parameters of the discrete copula model. A two-step procedure is proposed to estimate the parameters and predict the claim counts of the next period using the estimated parameters.